Four Scenarios of Malaysia-Indonesia Migration: From the Status Quo to the Wild Card Scenarios - Ladiqi, Suyatno; Bustami, Reevany; Nasruddin, Ellisha (Global Strategis, 2017)
In the context of ASEAN, the number of migrants from Indonesia and Malaysia is the largest. Combining the regular and the irregular migrants, the estimates range from 1.8 million to 3 million people. It is incontrovertible that movement of such magnitude has its impacts, probably both positive and negative. This article aims at providing an analysis based on future scenarios. The purpose is not to make predictions but rather to chart possible paths of critical events that would lead to different scenarios which have different implications to the political, economic and socio-cultural realities. Within this analysis, it is hoped that certain taken-for-granted blind-spots, due to conventional assumptions and mainstream paradigms, will be exposed and examined.